2009
DOI: 10.1176/ps.2009.60.11.1527
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Nurse-Initiated Care in a Mental Health Crisis Assessment and Treatment Team in Australia

Abstract: The findings indicate that the nurse practitioner role can potentially initiate safe and effective mental health care and treatment that is as satisfying as that initiated by a physician. Additional, larger-scale research is required to determine the generalizability of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Lanza et al's (2016) study of a violence prevention community meeting for reduction of inpatient aggression actually produced results suggesting small but significant increases in violence in the intervention group. In one study (Happell et al, 2009), there was a significant improvement in the staff‐rated global outcome in the mental health nurse‐delivered experimental study arm but, due to equal improvement in the control study arm, there was no significant between group improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Lanza et al's (2016) study of a violence prevention community meeting for reduction of inpatient aggression actually produced results suggesting small but significant increases in violence in the intervention group. In one study (Happell et al, 2009), there was a significant improvement in the staff‐rated global outcome in the mental health nurse‐delivered experimental study arm but, due to equal improvement in the control study arm, there was no significant between group improvement.…”
Section: Resultsmentioning
confidence: 99%
“…We contacted the corresponding authors of nine studies to request additional information on: 1. the clinical setting where fieldwork was conducted [ 29 , 30 , 31 ], 2. the population and sample size [ 30 , 31 , 34 , 37 , 41 , 55 ], 3. ethics approval [ 64 ] and 4. approach to data analysis [ 28 , 40 ]. As of the 27 June 2022, two authors, [ 28 , 37 ] responded, providing the requested information that we incorporated in the risk assessment data extraction tables, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies included both service users and carers, and five just carers. The total number of service users and carers involved in included studies was 1689 and 166 (the number of carers included was not reported in three studies [ 30 , 31 , 34 , 55 ] respectively). The median sample size for included studies was 15 (range, five to 511).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations